Low fruit and vegetable intake is associated with depression among Korean adults in data from the 2014 Korea National Health and Nutrition Examination Survey - Se-young Ju; Yoo Kyoung Park (BMC, 2019)
Abstract Background Depression is a major mental disorder worldwide. The prevalence of depression among Korean adults was estimated to be 5.6% in 2006 and 6.7% in 2011, and that increased to 10.3% in 2013. Using national data, the present study investigated the association between vegetable and fruit intake and the prevalence of depression among Korean adults. Methods This analysis used data from 4349 subjects aged 19 years and older who participated in the Korea National Health and Nutrition Examination Survey (KNHANES, 2014). Depression was assessed using the self-reported Patient Health Questionnaire (PHQ)-9. Food and nutrient intake was assessed using the 24-h recall method. Individual food intake was categorized into 18 food groups. The statistical analyses in this study were performed by adopting stratification, clustering, and sample weight variables using SPSS Ver. 23.0. Cronbach's α was used to determine the internal consistency of the PHQ-9 items. Logistic regression analysis was used to estimate the odds ratios of depression adjusted for several confounders. Results The depression rate of all subjects was between 8.7 and 4.7% and decreased as vegetable and fruit intake increased. With regard to sex, the depression rate decreased from 6.4 to 2.5% in males and from 11.4 to 6.6% in females as vegetable and fruit intake increased. Thus, the results of this study reveal an inverse association between vegetable and fruit intake and depression. The odds ratios show that vegetable and fruit intake was inversely associated with depression with no adjustment. When the data were adjusted for age, energy intake, obesity, smoking, drinking, stress, eating-out frequency, breakfast, and food security, subjects exhibited significantly lower rates of depression with higher vegetable and fruit intakes. Conclusions This is the first study to investigate the association between vegetable and fruit consumption and depression in a Korean population. Additional epidemiological studies are needed to find the underlying reasons for that association.